2022
DOI: 10.3390/polym14091730
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Essential Oils: A Review

Abstract: Essential oils (EOs) are complex mixtures of volatile compounds extracted from different parts of plants by different methods. There is a large diversity of these natural substances with varying properties that lead to their common use in several areas. The agrochemical, pharmaceutical, medical, food, and textile industry, as well as cosmetic and hygiene applications are some of the areas where EOs are widely included. To overcome the limitation of EOs being highly volatile and reactive, microencapsulation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 239 publications
(259 reference statements)
0
20
0
1
Order By: Relevance
“…However, most of the EOs are unstable and have an unpleasant odor, which hampers their application in the breeding industry 17 . Microencapsulation has been shown to protect EOs from oxidation and reduce the release of unpleasant odor 18 . We previously prepared a microencapsulated essential oil (MEEO) product containing 5% carvacrol, 2% thymol, and 3% cinnamaldehyde, and evaluated its effects on intestinal health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the EOs are unstable and have an unpleasant odor, which hampers their application in the breeding industry 17 . Microencapsulation has been shown to protect EOs from oxidation and reduce the release of unpleasant odor 18 . We previously prepared a microencapsulated essential oil (MEEO) product containing 5% carvacrol, 2% thymol, and 3% cinnamaldehyde, and evaluated its effects on intestinal health.…”
Section: Introductionmentioning
confidence: 99%
“…17 Microencapsulation has been shown to protect EOs from oxidation and reduce the release of unpleasant odor. 18 We previously prepared a microencapsulated essential oil (MEEO) product containing 5% carvacrol, 2% thymol, and 3% cinnamaldehyde, and evaluated its effects on intestinal health. The results showed that dietary supplementation with 100 mg kg −1 MEEO reduced the negative effects of the common EOs (unencapsulated), ameliorated the antioxidative capacity of the small intestine and promoted beneficial bacteria colonization in the large intestine of weaning piglets, while chlortetracycline (CTC) showed an adverse effect, suggesting that MEEO may help to improve intestinal health in a different way from CTC.…”
Section: Introductionmentioning
confidence: 99%
“…[73] In recent years, essential oils and other EOCs have been increasingly popular choices for inclusion in a wide variety of skin care products. Because of the potential benefits that compounds like these offer in terms of keeping youthful, healthy skin and insulating it from environmental damage [74,75], there has been a recent surge in the use of skincare products that contain compounds like these. EOs have a crucial role in the preservation of healthy skin, both in terms of the microbiota that live on the skin and the protective function that the stratum corneum provides [76].…”
Section: Application Of Essential Oil In Cosmeticmentioning
confidence: 99%
“…There are different types of disinfectants from various sources. Perfume oils (mixture of natural essential oils and odoriferous organic chemicals) were active in destroying microorganisms either by direct contact with the oils or their vapors [9] [10] [11] [12]. In addition, volatile compounds like trans-2-hexenal, 2,4-hexadienal, furfural, β-ionone, and 1-nonanal found to occur naturally in corn ears inhibit the growth of Aspergillus flavus [13].…”
Section: Introductionmentioning
confidence: 99%